‘Very Much the Tortoise’: A Review of The Slow Philosophy of J. M. Coetzee - Marc Farrant (Janeway JS, 2017)
A review of Jan Wilm’s The Slow Philosophy of J. M. Coetzee (2016).
Keywords: Violence; body; Sublime; Feminist; Abjection